Influence of progesterone application on trigeminal nerve root-entry zone remyelination in experiment - Yu. Yu. Chomolyak (Ukrainian Neurosurgical Journal, 2007)
The results of trigeminal nerve root-entry zone remyelination experimental study are presented. Original experimental model of trigeminal nerve root focal toxic demyelination was used. The assessment of trigeminal nerve root remyelination was done using electron microscopy and immunohystochemistry. It is identified, that local progesterone application at demyelination part of trigeminal nerve increased remyelination.